Perilaku Pembuangan Sampah Rumah Tangga Masyarakat Jalan Kesehatan Gampong Drien Rampak Johan Pahlawan Aceh Barat - Shaibathul Aslamiyah; Kiswanto Kiswanto; Onetufifsi Putra; Wintah Wintah; Firman Firdaus Saputra (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Garbage is a source of disease for humans living around garbage dumps. One location used as a garbage dump by irresponsible people is on Jalan Kesehatan, Gampong Drien Rampak, Johan Pahlawan District, West Aceh Regency. The presence of garbage at this location, according to researchers, is due to a lack of public awareness of environmental health, especially the impacts of indiscriminate garbage disposal. The purpose of this study was to examine the behavior of the Jalan Kesehatan community regarding environmental health from household waste. This study used a qualitative research type, data collection was carried out through interviews and observations, and data analysis was carried out using descriptive qualitative methods. The results of the study can be concluded that the Jalan Kesehatan community currently has very good behavior regarding environmental health from household waste. Therefore, the Jalan Kesehatan community has made various efforts to overcome the presence of garbage on Jalan Kesehatan, such as reprimanding people who throw garbage, coordinating with the Environmental Agency, and also helping to clean the location from garbage with the West Aceh Environmental Agency.